COMMUNITY EMPOWERMENT DALAM PENGELOLAAN BANK SAMPAH DI KELURAHAN REJOWINANGUN SELATAN - Amelia Intan Zahra; Joko Tri Nugraha; Tri Asih Wismaningtyas; Fadlurrahman Fadlurrahman (Jurnal Progress Administrasi Publik, 2026)
This research is motivated by the absence of research that specificially examines community empowerment in waste banks in Rejowinangun Selatan Subdistrict, which is recorded as having the highest daily waste volume in South Magelang District and still facing sereval challenges in its menagement. Therefore, this study aims to analyze the stages of community empowerment in waste bank management, specifically at Bank Sampah Ismoyo Makmur (BSIM) and Bank Sampah Edellweis (BSE). This research employs a qualitative method with a case study approach. Informants were selected using purposive sampling, involving several relevant stakeholders. Data analysis was conducted interactively through data collection, data condensation, data display, and conclusion drawing. The results show that the stages of community empowerment at BSIM and BSE have been implemented in accordance with the framework proposed by Suharto (2014) and Suprayogi (in Suaib, 2023), which consists of enabling, empowering, and protecting. However, the implementation has not been fully optimal. The enabling stage has encouraged initial public awareness, but participation remains limited. The empowering stage shows variations in achievement and faces constraints in capacity building and access to external support. Meanwhile, the protecting stage has reached an initial maintenance phase, yet the sustainability of activities still depends on the commitment of the management. The main finding of this research indicates that community empowerment is a gradual and continuous process influenced by internal capacity, external support received by the waste banks, and the social conditions of the community. Keywords: Community Empowerment; Rejowinangun Selatan; Waste Bank